Suspension- and powder-based derivation of Hansen dispersibility parameters for zinc oxide quantum dots - Süß, Sebastian; Lin, Wei; Getmanenko, Olga; Pflug, Lukas; Sobisch, Titus; Peukert, Wolfgang; Lerche, Dietmar; Segets, Doris (Particuology, 2019)
For most particle-based applications, formulation in the liquid phase is a decisive step, and thus, particle interactions and stability in liquid media are of major importance. The concept of Hansen solubility parameters (HSP) was initially invented to describe the interactions of (polymer) molecules and their solubility in different liquids and is increasingly being used in particle technology to describe dispersibility. Because dispersions are not thermodynamically stable, the term Hansen dispersibility parameters (HDP) is used instead of HSP (Süß, Sobisch, Peukert, Lerche, & Segets, 2018). Herein, we extend a previously developed standardized and non-subjective method for determination of Hansen parameters based on analytical centrifugation to the important class of quantum materials. As a technically relevant model system, zinc oxide quantum dots (QDs) were used to transfer our methodology to nanoparticles (NPs) with sizes below 10 nm. The results obtained using the standard procedure starting from a dried powder were compared with those obtained through redispersion from the wet sediment produced during the typical washing procedure of QDs, and drying was observed to play an important role. In conclusion, our study reveals the high potential of HDP for quantifying the interfacial properties of NPs as well as their link to dispersibility.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Colloidal stability; Functionalization; Hansen solubility parameter; Quantum material; Semiconductor nanoparticles